Pengaruh Human Capital dan Green Investment terhadap ESG pada Emiten LQ45 Indonesia - Aulia Jihan Maulani; Dwi Jayanti (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of Human Capital and Green Investment on the Environmental, Social, and Governance (ESG) Risk Rating of companies listed in the LQ45 index on the Indonesia Stock Exchange for the 2020–2023 period. This study uses a quantitative approach with multiple linear regression. The sample was selected through a purposive sampling technique, with a total of 13 companies meeting the criteria and resulting in 72 observations over four years. The results show that Human Capital has a negative and significant effect on the ESG Risk Rating. Conversely, Green Investment does not have a significant effect on the ESG Risk Rating. These results emphasize the importance of strengthening a company's internal factors, particularly in the aspect of human resource development, to improve sustainability performance.